OP0209 Soluble Ephrin-B2 Ectodomain Contributes to the Pathogenesis of Systemic Sclerosis. (9th June 2015) - Lagares, D.; Ghassemi-Kakkaroodi, P.; Tremblay, C.; Wu, J.; Ahluwalia, N.; Probst, C.K.; Barry, S.; Black, K.E.; Montesi, S.; Blati, M.; Baron, M.; Fahmi, H.; et al.
Abstract : Background: Fibrotic diseases including systemic sclerosis (SSc) or scleroderma are characterized by fibroblast differentiation into myofibroblasts and extracellular matrix deposition. The mechanisms driving fibroblast activation are not fully known, and the identification of new profibrotic mediators will hopefully lead to the development of new rational anti- fibrotic treatments. Microarray studies show that ephrin-B2 is overexpressed in SSc fibroblasts, suggesting that this cell- membrane-anchored ligand may be a novel profibrotic mediator. Objectives: To identify the role of ephrin B2 in skin and lung fibrosis. Methods: Mice were injected subcutaneously with recombinant mouse ephrin-B2/Fc (100μg/kg/mouse) daily for two weeks and assessed for the development of skin fibrosis. Fibroblast-specific ephrin-B2 knockout (KO) mice were generated and assessed for the development of lung and skin fibrosis induced by intratracheal or subcutaneous injection of bleomycin respectively, by histology, hydroxyproline levels, q-PCR and western blot. Ephrin-B2 levels were determined by western blot and ELISA in broncoalveolar lavage (BAL) fluids from these mice, and from humans with SSc. Cultured mouse and human skin fibroblasts were treated with recombinant ephrin-B2-Fc (0.1-5 mg/mL) and the expression of profibrotic genes was assessed by qPCR and western blot. 96-Multiwell Insert Systems (BD Biosciences) were used to measure the chemotaxis of mouse skin fibroblasts from mice treated with either PBS or bleomycin for 7 days. Fibroblasts in these chemotaxis experiments were transfected with 20nM siRNA (Dharmacon) targeting EphB2, EphB3 or EphB4 receptors. Non-targeting siRNA was used as a control. Results: Treatment of normal human skin fibroblasts with recombinant ephrin-B2 in vitro induced myofibroblast differentiation, as indicated by increased stress fiber formation, increased expression of α-SMA and collagen type I. Mice treated sub-cutaneously with recombinant mouse ephrin-B2/Fc exhibited significant skin fibrosis indicated by increased dermal thickness, collagen deposition, hydroxyproline content and α-SMA-expressing myofibroblasts. Fibroblast-specific ephrin-B2 KO mice were significantly protected from bleomycin-induced lung and skin fibrosis, as indicated by significant reductions in hydroxyproline and TGF-b levels. Q-PCR and immunohistochemical analyses showed that ephrin-B2 expression was elevated in SSc fibroblasts and skin sections from IPF patients respectively. Soluble ephrin-B2 levels determined by ELISA and western blot were increased in BAL from SSc patients and bleomycin-challenged mice. Soluble ephrin-B2 induced fibroblast chemotaxis (through EphB3/EphB4 but not EphB2 receptors), suggesting that pathological shedding of soluble ephrin-B2 might account for the profibrotic effect of this ligand in lung and skin fibrosis. Conclusions: Our study identifies ephrin-B2 as a novel mediator of fibrogenesis, and suggests that targeting ephrin-B2 ligand or its binding receptors EphB3/EphB4 could potentially be a new therapeutic strategy in SSc. Disclosure of Interest: None declared